BOLOGNA PROCESS: 15 YEARS LATER - Galina N. Motova (Высшее образование в России)
The article gives an analysis of the main documents adopted by the Ministers of Education of the EHEA at the meeting in Yerevan (the Republic of Armenia). It highlights the problems and challenges that national systems of higher education are facing; it also defines the priorities and commitments of the Bologna-countries in promoting cooperation and integration as part of the EHEA. Special focus is made on the statistical data analysis and the national reports on the implementation of the principles lying within the European agreements for the current decade. A key factor in ensuring mutual trust and establishing the EHEA is the availability of a multi-level quality assurance system: institutional, national, European. The author reinforces the need for reviewing and approving the revised Standards and Guidelines for Quality Assurance in the EHEA (ESG).